2016
DOI: 10.1179/1743294414y.0000000337
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and corrosion resistance of ZnO/CeO2 composite films

Abstract: Zinc oxide/cerium oxide (ZnO/CeO 2 ) composite films were fabricated on zinc surfaces by electrochemical oxidation at different current densities. Scanning electron microscopy and X-ray photoelectron spectroscopy were used to investigate the surface compositions and morphologies of the films. Corrosion resistance was analysed using polarisation curves, open-circuit potential and electrochemical impedance spectroscopy. The X-ray photoelectron spectra showed that the films were composed of ZnO and CeO 2 . Evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Figure 1(a) shows that the different polygon shaped micro crack pieces are uniformly distributed in the conversion coating without microcapsules. The micro crack may be caused by the stress release during the process of conversion coating treatment, which can be easily seen in previous works [4][5][6].…”
Section: Morphology and Composition Of Conversion Coatingmentioning
confidence: 73%
See 2 more Smart Citations
“…Figure 1(a) shows that the different polygon shaped micro crack pieces are uniformly distributed in the conversion coating without microcapsules. The micro crack may be caused by the stress release during the process of conversion coating treatment, which can be easily seen in previous works [4][5][6].…”
Section: Morphology and Composition Of Conversion Coatingmentioning
confidence: 73%
“…Figure 1(a) shows that the different polygon shaped micro crack pieces are uniformly distributed in the conversion coating without microcapsules. The micro crack may be caused by the stress release during the process of conversion coating treatment, which can be easily seen in previous works [4-6]. From Figure 1(b), many microcapsules are distributed in the region of cracks, and most of the microcapsules are about 30–50 µm in diameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have reported that co-deposition of mixed metal oxides such as ZnO:CeO 2 could yield mixtures of exceptional properties such as high UV absorption, controllable optical band gap, good photoluminescence, high extinction coefficient, anticorrosive properties and high refractive index [28]. In recent years, ZnO:CeO 2 mixed oxides thin films have been used for essential applications, such as sensors [29,30], catalysts [31,32], fuel cells applications [33], antibacterial applications [34], corrosion protective coating [35], and UV filters [36].…”
Section: Introductionmentioning
confidence: 99%